Critical motivation factors among project managers to achieve successful project in Malaysian construction industry / Farhan Md Dahlan ... [et al.] - Farhan, Md Dahlan; Muhammad Amirul Fahme, Ahmad; Siti Nadiah, Mohd Ali; Siti Sarah, Mat Isa; Norbaizura, Abu Bakar (2015)
Motivation is inspiration that moves behavior and guide individuals to achieve desired goals. Motivation is very important especially to the project managers to ensure the commitment and interest towards job as well as professionalism and disciplined. Therefore, research has been conducted to identify the critical motivation factors among project managers to achieve successful sustainability growth in Malaysian construction industry. This research was started out by reviewing literature from journals, books and web pages. Surveys using questionnaires forms were carried out to project managers from G7 contractors firms‟ in Klang Valley. Analysis using descriptive analysis reveals that the critical motivation factors are responsibility, manager competency, compensation or rewards and salary, employee development, appreciation and recognition, personal development, empowerment, interpersonal interaction, task, general working condition, mental and physical strength and ability of the project managers to use project management technique for process planning. This paper provides an insight for critical motivation factors among project managers from G7 contractors firm to successfully sustain the growth of construction industry. Although the research was carried out in Klang Valley, the results may be applicable to other states as well.